Interpretation of the concept of «modernization» in the context of sustainable development of economic entity - Yu. G. Borodin; E. I. Khabarova (Тонкие химические технологии, 2013)
Veral definitions of modernization "in general" were considered in order to develop an understanding of modernization at the level of a particular company (micro level). Modernization is a process of transforming a company into more modern condition characterized by the use of advanced technologies and the application of good practices of labor and production, leading to increased competitiveness. Today companies are under the influence of an ever-changing environment and increasing competitive pressures. This leads to the necessity of determining the long-term prospects, or "strategic management", and to ensure competitive advantages in the future. Companies should consider modernization as a strategy of development. The situation in Russia in the last decade requires the action of the modernization of economy by modernizing its structural units – companies, according to the statements of the top officials of the country, paying attention to the complexity of the modernization and the need to involve all sectors of the economy in the process. Additionally, because the technological backwardness leads to increased negative impacts on the environment, modernization should be considered in the context of sustainable development.